The Influence of Total Quality Management on Operational Performance at Rayz UMM Malang Hotel - Alma Karistiana; R Y Susanto; Yuni Setyawati (International Research & Development for Human Beings (IRDH), 2026)
The purpose of this research is to determine the effect of total quality management on operational performance at Hotel Rayz UMM Malang. This is a quantitative study. The sampling method used in this research is random sampling with 47 respondents. Data collection techniques include observation, questionnaires, literature studies, and documentation. The data analysis method is simple linear regression. The research results prove that total quality management has a significant and positive effect on operational performance at Hotel Rayz UMM Malang, as indicated by a calculated t value of 6.440, representing an influence of 66.4%. The aspects of total quality management that affect operational performance include employees focusing on providing good service to customers, conducting evaluations for continuous service improvement, employees receiving training programs for skill development, and good communication between management and employees.